2004
DOI: 10.1126/science.1094113
|View full text |Cite
|
Sign up to set email alerts
|

Functional Conversion Between A-Type and Delayed Rectifier K + Channels by Membrane Lipids

Abstract: Voltage-gated potassium (Kv) channels control action potential repolarization, interspike membrane potential, and action potential frequency in excitable cells. It is thought that the combinatorial association between distinct alpha and beta subunits determines whether Kv channels function as non-inactivating delayed rectifiers or as rapidly inactivating A-type channels. We show that membrane lipids can convert A-type channels into delayed rectifiers and vice versa. Phosphoinositides remove N-type inactivation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
262
4
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 305 publications
(287 citation statements)
references
References 37 publications
17
262
4
1
Order By: Relevance
“…Because PIP 3 inhibition requires residues 61-90 and prevents Ca 2ϩ ͞CaM regulation, we postulate that PIP 3 binding may anchor the N terminus of CNGA2 to the membrane surface, thereby disrupting the intersubunit autostimulatory interaction. This molecular mechanism resembles that recently proposed for prevention of K ϩ channel N-type inactivation by phosphoinositides: sequestering of the Nterminal domain at the cytoplasmic face of the membrane (31). Although the N terminus of CNGA3 can bind both PIP 3 and Ca 2ϩ ͞CaM, these interactions appear to be functionally silent, most likely reflecting the absence of a pronounced autostimulatory interaction with the C terminus (27).…”
Section: Discussionmentioning
confidence: 79%
“…Because PIP 3 inhibition requires residues 61-90 and prevents Ca 2ϩ ͞CaM regulation, we postulate that PIP 3 binding may anchor the N terminus of CNGA2 to the membrane surface, thereby disrupting the intersubunit autostimulatory interaction. This molecular mechanism resembles that recently proposed for prevention of K ϩ channel N-type inactivation by phosphoinositides: sequestering of the Nterminal domain at the cytoplasmic face of the membrane (31). Although the N terminus of CNGA3 can bind both PIP 3 and Ca 2ϩ ͞CaM, these interactions appear to be functionally silent, most likely reflecting the absence of a pronounced autostimulatory interaction with the C terminus (27).…”
Section: Discussionmentioning
confidence: 79%
“…Dashed lines represent standard errors of the mean (n ϭ 6). activity (41). We find that incubating rodent and human pancreatic islet ␤-cells with low micromolar concentrations of AA results in accelerated inactivation of their delayed rectifier Kvlike currents (Figs.…”
Section: Discussionmentioning
confidence: 98%
“…Arachidonic acid causes other slowly inactivating delayed rectifier K ϩ channels, such as Kv3.4, to resemble fast inactivating A-type K ϩ currents (41). The phospholipid content of esterified AA is higher in pancreatic islets than in other tissues (23,25,26,29), and arachidonate is hydrolyzed from phospholipids upon stimulation of islets with secretagogues (13,14,27,31,36,44) and accumulates to micromolar concentrations (7,27,28) that are sufficient to modulate delayed rectifier Kv channel FIGURE 5.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the inactivation time constant of Kv␤1.1 was changed from Ͻ10 ms to a slow inactivation of hundreds of milliseconds. Oliver et al (33) recently also reported that membrane lipids can regulate inactivation of Kv1.1͞Kv␤1.1 by converting A-type channels into delayed rectifiers, and vice versa. The bidirectional control of Kv1.1͞Kv␤1.1 inactivation by lipids is mediated through immobilizing͞mobilizing the ␤ ball domain, suggesting a common mechanism for a dynamic regulation of neuronal excitability (33).…”
Section: Discussionmentioning
confidence: 99%